PENGARUH KOMPETENSI WIRAUSAHAWAN TERHADAP KINERJA USAHA MIKRO KECIL MENENGAH KOTA MADIUN DENGAN PEMBIAYAAN BANK SEBAGAI VARIABEL INTERVENING - Satriabayu Rifantama; Diah Hari Suryaningrum (Jurnal Proaksi, 2022)
UMKM have a very important role in the economic sector and can be considered as the backbone of the economy in Indonesia, and the strong and dynamic character of UMKM can encourage the development of the nation's economy. The purpose of this study was to examine and analyze the effect of Entrepreneurial Competence, and Bank Financing as intervening variables on MSME Business Performance. The population in this study is all UMKM in Madiun City in 2020 as many as 36.555 UMKM. Researchers took samples using purposive sampling technique. The sample that researchers used in this study was 126 research samples. The analysis used in this research is partial least square. Based on the results of the study, it can be concluded that the entrepreneurial competence variable influences and contributes to the business performance of UMKM in UMKM in Madiun City. Entrepreneurial competence influences and contributes to bank financing for UMKM in the city of Madiun. Competence of entrepreneurs with bank financing as an intervening variable affects the business performance of UMKM in UMKM in the city of Madiun. The implications and suggestions are that entrepreneurs/entrepreneurs should monitor the movement of MSME business performance from year to year often to maintain the age of UMKM so that they continue to run over time. Keywords: Entrepreneurial Competence, Financing, UMKM Performance.